Host competence of the African rodents Arvicanthis neumanni, A. niloticus and Mastomys natalensis for Leishmania donovani from Ethiopia and L. (Mundinia) sp. from Ghana. (April 2020) - Sadlova, Jovana; Vojtkova, Barbora; Becvar, Tomas; Lestinova, Tereza; Spitzova, Tatiana; Bates, Paul; Volf, Petr
Abstract: Visceral leishmaniasis caused by Leishmania donovani is regarded as mostly anthroponotic, but a role for animal reservoir hosts in transmission has been suggested in East Africa. Field studies in this region have shown the presence of this parasite in several mammalian species, including rodents of the genera Arvicanthis and Mastomys . Further, the natural reservoirs of Leishmania ( Mundinia) sp. causing human cutaneous disease in Ghana, West Africa, are unknown. This study assessed the potential role of the Sub-Saharan rodents Arvicanthis neumanni, A. niloticus and Mastomys natalensis as hosts of L. donovani and L. sp . from Ghana, based on experimental infections of animals and xenodiagnoses. The distribution and load of parasites were determined post mortem using qPCR from the blood, skin and viscera samples. The attractiveness of Arvicanthis and Mastomys to Phlebotomus orientalis was tested by pair-wise comparisons. None of the animals inoculated with L. donovani were infectious to P. orientalis females, although, in some animals, parasites were detected by PCR even 30 weeks post infection. Skin infections were characterized by low numbers of parasites while high parasite burdens were present in spleen, liver and lymph nodes only. Therefore, wild Arvicanthis and Mastomys found infected with L. donovani, should be considered parasite sinks rather than parasite reservoirs. This is indirectly supported also by results of host choice experiments with P. orientalis in which females preferred humans over both Arvicanthis and Mastomys, and their feeding rates on rodents ranged from 1.4 to 5.8% only. Therefore, the involvement of these rodents in transmission of L. donovani by P. orientalis is very unlikely. Similarly, poor survival of Leishmania parasites in the studied rodents and negative results of xenodiagnostic experiments do not support the involvement of Arvicanthis and Mastomys spp. in the transmission cycle of L. sp. from Ghana. Graphical abstract: Image 1 Highlights: Three species of Sub-Saharan rodents were infected and xenodiagnosed. Skin infections in Arvicanthis and Mastomys were characterized by low parasite loads. None of animals inoculated with leishmania were infectious to sand flies. Phlebotomus orientalis females significantly preferred man over rodents. Rodents are unlikely to be involved in the circulation of the two studied Leishmania in nature.